Integrasi Nilai Islami Dalam Tata Kelola Digital Di Madrasah Tsanawiyah Al Mufasir - Aisah, Deuis; Safwandy Nugraha, Mulyawan (JURNAL MANAJEMEN PENDIDIKAN, 2025)
Integration of Islamic Values in Digital Governance at Madrasah Tsanawiyah Al MufasirThe development of digital technology has brought significant changes to the education management system, including in the Madrasah Tsanawiyah (MTs) environment. Digitalization is now a key element in the governance of educational institutions, demanding efficiency, transparency, and data-driven accountability. However, as Islamic educational institutions, madrasas have a responsibility to ensure that digital transformation remains grounded in Islamic moral and spiritual values. This study aims to explore the application of Islamic digital ethics principles in digital governance at Madrasah Tsanawiyah Al Mufasir, Jln. Gandasoja No. 41, Sukamantri Village, Paseh District, Bandung Regency. The focus of the study includes the internalization of the values of amanah (responsibility), shiddiq (honesty), ‘adl (justice), and ihsan (professionalism) in various aspects of digital management such as the Madrasah Information System, online learning, and application-based administration. The results of the study indicate that the integration of these Islamic values not only improves the efficiency and quality of digital governance but also strengthens institutional ethics and the religious character of all madrasah members. Thus, digitalization at MTs Al Mufasir is not merely a technological instrument, but also a means of preaching and fostering noble character. This research is expected to serve as a reference in developing an Islamic digital governance model based on Islamic values (Islamic Digital Governance Model) at other Islamic educational institutions.